The area of a trapezoid is 322m2 one base is 12m and the height 14m what is the measure of the other base

Answers

Answer 1
Answer:

Answer:

b = 34m

Step-by-step explanation:

Answer 2
Answer:

Answer:

Depends on which base you mean, the longer base would be b=41.67

The shorter base would be a=39.67

Hope this helps :)


Related Questions

If you run 6. Miles an hour how long will it take to do 18 miles help quick pls
A text font fits 12 characters per inch. Using the same font, how many characters can be expected per yard of text?
According to the Rational Root Theorem, the following are potential fox) 2x2 +2x 24.roots of -4, -3, 2, 3, 4Which are actual roots of f(x)?O 4 and 34, 2, and 3O 3 and 43, 2, and 4
What is the surface area of the prism? A. 138 yd2 B. 192 yd2 C. 264 yd2 D. 272 yd2
Match the expressions 21/25 60% 13/20 84% 2/5 75% 65% 3/4 3/5

What single decimal multiplier would you use to increase by 4% followed by a 3% increase

Answers

Answer:

1.0712

Step-by-step explanation:

if you increase by 4%, it means you will have a new total of 104%. In decimals it is 1.04 (divide your percentage by 100) after that you do the same with the 3% increase. you'll have a new total of 103%. In decimals 1.03. If you want to know what single multiplier you can use, you need to multiply the both decimals. So you get 1.04 x 1.03 = 1.0712

hope this will help you, have a nice day!

Charlie has a piece of toast that has cream cheese on one side, and he dropped it once. One time, it landed with the cream cheese side up. If he drops it two more times, what is the probability that it will have landed cream cheese side up a total of three times?one over four
one over three
one over eight
three over four

Answers

Answer: first option, 1/4.

Explanation:

1) Every drop is an independent event. So, the joint probability is the product of the individual probabilities.

2) The fact that the piece ot toast landed once time with the cream cheese side up, does not affect the next two drops.

3) Since, the piece of toast landed the first time with cream cheese side up, the probability that it it will have landed cream cheese side up a total of three times is the probability that it will have landed two more times with cream cheese side up.

3) The probability that the piece of toast will have landed cream cheese side up two more times is 1/2 × 1/2 = 1/4. And that is the answer to the question.

Just multiply the probability of each instance together (in fraction form). 1/2 * 1/2 * 1/2 = 1/8.
However, be aware that this only works because it asked what the probability of it happening three times in a row. For example, if the question read, "What is the probability of this piece of bread landing butter side down, assuming it has already landed three times butter side down?", the answer would be 1/2 because the probability of previous incidents do not actually physically affect a future test.

If you have complementary angles and one angle is 83°, what is the other angle?

Answers

Answer:

7 degrees

Step-by-step explanation:

90-83=7

Answer:

7 degrees

Step-by-step explanation:

complementary angles are equal to 90

6+2(5-3a)=2a(2+8).....

Answers

4000 hope I helped you

Sin78 ×cos42+cos78×sin42 evaluate without the use of a calculator

Answers

sin a * cos b + cos a * sin b=sin (a+b)

sin 78 * cos 42 + cos 78* sin 42=sin (78+42)=sin 120=sin(180-120)=
sin 60=√3 / 2

Answer: sin 78 * cos 42 + cos 78* sin 42=√3 / 2

Please help, thank you!Match the sequence and recursive expression to its explicit expression. f(n) = 2n + 10

{2, 4, 6, 8...} ...} f(1) = 2 and f(n) = f(n - 1) + 2 for n >


{12, 14, 16, 18...} f(1) = 12 and f(n) = f(n - 1) + 2 for n > 1

Answers

Given:

f(n)=2n+10

To find:

The sequence and recursive expression to the given explicit expression.

Solution:

We have,

f(n)=2n+10

For n=1,

f(1)=2(1)+10

f(1)=2+10

f(1)=12

The value of f(1) is 12.

Similarly,

For n=2,

f(2)=2(2)+10=14

For n=3,

f(3)=2(3)+10=16

For n=4,

f(2)=2(4)+10=18

The required sequence is {12,14,16,18,...}.

The recursive expression of an AP is

f(n)=f(n-1)+d

where, d is common difference.

Here d=2,

f(n)=f(n-1)+2

Therefore, the recursive expression is f(n)=f(n-1)+2.